The Effect of Conservative Immobilization and Vitamin D in Distal Radius Buckle Fracture Healing in a Child: A Case Report: Penelitian - Rizaldy, Muhammad Irfan; Rahmawati , Amalia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Distal radial buckle fractures are the most common forearm injuries in children and generally heal well with conservative management. Vitamin D plays a crucial role in calcium metabolism and bone mineralization, although its influence on the rate of fracture healing in children remains controversial. We report the case of a 3-year-old child with a distal radial buckle fracture following a fall from a standing position. The patient was treated conservatively with short-arm immobilization and empiric vitamin D supplementation (400 IU twice daily) without serum levels being measured. After 4 weeks, radiographs showed significant callus formation and full recovery. Conservative immobilization remains the gold standard due to its excellent outcomes with minimal complications. Although evidence for the effectiveness of vitamin D is inconsistent, it biologically supports bone formation through osteoblast differentiation, collagen synthesis, and calcium balance. In populations with mild vitamin D deficiency, supplementation can accelerate callus formation and improve radiographic findings. This case demonstrates early callus formation, likely influenced by the synergistic effect of immobilization and vitamin D. Conservative management is effective for buckle fracture healing, and vitamin D supplementation, even in the absence of confirmed deficiency, may promote bone remodeling and accelerate healing.